Implementasi Manajemen Program Tahfidz Alfiyyah Di Pondok Pesantren Gemayasih Cibungur Tasikmalaya - Nina Nurlaila; Ahmad Hinayatulohi; Icha Apriliza (CV. Biha Cendekia, 2025)
This research is motivated by the urgency of preserving and mastering the science of nahwu through the memorization method of Ibn Malik's Matan Alfiyyah, which is an important reference in the study of classical Arabic grammar in Islamic boarding schools. Gemayasih Cibungur Tasikmalaya Islamic Boarding School is one of the institutions that implements the Alfiyyah tahfidz program in a structured manner in its Islamic boarding school curriculum. The purpose of this study is to describe and analyze the implementation of the Alfiyyah tahfidz program management which includes aspects of planning, implementation, and evaluation. This study uses a qualitative approach with a case study method. Data collection techniques are carried out through participatory observation, in-depth interviews with the boarding school leader, program managers, and students, as well as documentation of learning and assessment activities. The results show that the management of the Alfiyyah tahfidz program at Gemayasih Islamic Boarding School is carried out with careful planning through student selection, scheduling, and the preparation of memorization targets. The program implementation is supported by a classical approach and a talaqqi-musyafahah system, as well as strict supervision through routine deposits and periodic examinations. Evaluation was conducted both formatively and summatively, focusing on memorization and comprehension. Overall, the program's management implementation was effective and fostered the development of a cadre of students who excel in mastering the science of nahwu in a deep and contextual manner.